2023
DOI: 10.3934/publichealth.2023006
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of laboratory and rehabilitation specialists during COVID-19: A rapid review

Abstract: <abstract><sec> <title>Backgrounds</title> <p>Healthcare workers have experienced considerable stress and burnout during the COVID-19 pandemic. Among these healthcare workers are medical laboratory professionals and rehabilitation specialists, specifically, occupational therapists, and physical therapists, who all perform critical services for the functioning of a healthcare system.</p> </sec><sec> <title>Purpose</title> <p>This rapid review exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…They indicate the need to include in prevention strategies: promotion of interprofessional relations, clear definition of the role of the physiotherapist, multidisciplinary education, support staff and innovative models of care [32]. Review by Ishaky et al showed that in future emergencies such as a pandemic, providing timely and accurate health information to healthcare professionals is crucial, and will translate into improved mental health outcomes, including stress and burnout [33]. A review by Weenink et al showed that despite including 38 studies on remediation and rehabilitation for healthcare professionals with performance problems (dentists, midwives, nurses, pharmacists, doctors, physiotherapists, psychologists and psychotherapists), comparisons of outcomes between professions and specific performance problems cannot be made.…”
Section: Reference To Results Of Other Studiesmentioning
confidence: 99%
“…They indicate the need to include in prevention strategies: promotion of interprofessional relations, clear definition of the role of the physiotherapist, multidisciplinary education, support staff and innovative models of care [32]. Review by Ishaky et al showed that in future emergencies such as a pandemic, providing timely and accurate health information to healthcare professionals is crucial, and will translate into improved mental health outcomes, including stress and burnout [33]. A review by Weenink et al showed that despite including 38 studies on remediation and rehabilitation for healthcare professionals with performance problems (dentists, midwives, nurses, pharmacists, doctors, physiotherapists, psychologists and psychotherapists), comparisons of outcomes between professions and specific performance problems cannot be made.…”
Section: Reference To Results Of Other Studiesmentioning
confidence: 99%
“…The findings indicated that direct involvement in the care of COVID-19 patients is associated with higher levels of state anxiety, suggesting that physicians who directly engage with COVID-19 patients may experience heightened stress and emotional strain levels. Research findings have demonstrated a significant incidence of psychological symptoms [36] and burnout [37][38][39][40] among physicians during the COVID-19 pandemic. They exhibited greater symptoms of mental health problems by exceeding clinical thresholds for state anxiety, psychological distress (i.e., depression, anxiety, and stress), post-traumatic stress symptoms, and a high prevalence of burnout (i.e., emotional exhaustion, depersonalization, and diminished personal accomplishment) [6,20,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Some were only employed for the duration of the pandemic. It should be no surprise to readers of this journal that medical laboratory scientists have also been prone to the mental health consequences of the pandemic [2]. A recent Canadian survey of medical residents in laboratory medicine found high levels of burnout and depression [3].…”
Section: Full-textmentioning
confidence: 99%